Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4103/0970-0358.96572
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of eyelid malignancies - A review of 85 cases

Abstract: Background:Resection of eyelid malignancies leads to complex reconstructive problems due to the functional and aesthetic importance of an eyelid. Hence, a large number of such cases are referred to plastic surgery facilities. Eyelid malignancies are of varied histological types and the western and Asian data have considerable variations in case distribution and presentation. This study is an attempt to characterise these tumours in the Indian population.Materials and Methods:The present study is a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 12 publications
5
42
1
4
Order By: Relevance
“…In Western countries, Basal cell carcinoma is the commonest malignant eyelid tumour accounting for 80-90 % of eyelid cancers followed by Squamous cell carcinoma and Sebaceous gland carcinoma[1,7].Increased incidence of Sebaceous gland carcinoma and reduced Basal cell carcinoma might be attributed to oily skin and more melanin pigment in Indian population. At the same time, a decline in basal cell carcinoma and squamous cell carcinoma can be due to increased melanin which provides protection from damaging sunrays.Sebaceous gland carcinoma was more common in females and upper eyelid in the present study and same results were shown in studies bySushma TA et al, Mary HO et al, Kale SM et al, Kaliki S et al and Wang JC et al, justifying the fact that Sebaceous glands are more in upper eyelids than lower eyelids[1,14,20,24,23]. Lin et al described a significantly higher incidence of Sebaceous gland carcinoma in Taiwan…”
supporting
confidence: 90%
“…In Western countries, Basal cell carcinoma is the commonest malignant eyelid tumour accounting for 80-90 % of eyelid cancers followed by Squamous cell carcinoma and Sebaceous gland carcinoma[1,7].Increased incidence of Sebaceous gland carcinoma and reduced Basal cell carcinoma might be attributed to oily skin and more melanin pigment in Indian population. At the same time, a decline in basal cell carcinoma and squamous cell carcinoma can be due to increased melanin which provides protection from damaging sunrays.Sebaceous gland carcinoma was more common in females and upper eyelid in the present study and same results were shown in studies bySushma TA et al, Mary HO et al, Kale SM et al, Kaliki S et al and Wang JC et al, justifying the fact that Sebaceous glands are more in upper eyelids than lower eyelids[1,14,20,24,23]. Lin et al described a significantly higher incidence of Sebaceous gland carcinoma in Taiwan…”
supporting
confidence: 90%
“…The most common location of all malignant tumors in this study was the lower eyelid (74%), which has been reported in previous studies. [2,12,19,24] Patients with SGC showed very strong preference for upper eyelid (83.3%).The lower eye lid was also the most common site for all histological subtypes except SGC.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Studies by Paul S et al, Cook BE Jr et al, Deprez et al reported 71.8%, 90.8% and 86% BCC respectively, which was the most common malignant tumor in their case series. [3][4][5] However reports from central India(Sihota et al (30%), Jahagirdar S S et al (44.5%), Kale SM et al (48.2%) [17,18,19] show a relatively lower incidence of BCC. In our cases series BCC accounted for 26.3% and was the 2 nd most common malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations